Integrasi Pendidikan Keluarga dan Pendidikan Islam dalam Pengembangan Kepribadian Anak - Faisal Kamal; Robingun Suyud El Syam; Abdur Rofik; Siti Wulan Asih (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
This study discusses Islamic education looking at the role of parents in developing a child's personality, as well as what materials and methods are appropriate for developing a child's personality. Article type of literature or qualitative research. The primary data source takes the Prophet's hadith about nature in the Sahih Muslim Book and then analyzes it with support from secondary sources as explanatory. Data collection techniques from documentation to then be analyzed using inductive, deductive and ijmali interpretation methods. Research has shown that Islamic education is related to the role of parents in developing a child's personality, not only providing material, but must develop the potentials that have been brought by the child from birth so that the personality grows and develops optimally, both physically and spiritually, so that it is formed complete personality to become a good and perfect Muslim person.